THE EFFECT OF HEALTH INFRASTRUCTURE DEVELOPMENT, EDUCATION, AND THE NUMBER OF POPULATIONS ON ECONOMIC GROWTH IN NORTH SUMATERA PROVINCE - Mariyatul Kubtiyah Ritonga; Anhar Fauzan Priyonob (Quantitative Economics Journal, 2019)
Economic Growth in North Sumatera priod 2000 until 2012 shows the condition that increases continuously, but the increase did not have an impact on education, health. This study aimed to analyze the influence of the health infrastructure, education infrastructure and population to economic growth in the province of North Sumatra simultaneously and partially. The data used are secondary data from BPS in North Sumatra time series from 2000 till 2012. Data analysis was performed by using OLS (Ordinary Least Square) with a multiple linear regression models estimated with the help of the program Eviews 7. The results of this study showed that simultaneous variable health infrastructure, education infrastructure and population have a significant effect on economic growth in the province North Sumatra. While partially concluded that variable infrastructure and population health positive and significant effect; educational infrastructure but not significant positive effect on economic growth in the province of North Sumatra. The results of this study also showed that the most dominant variables to economic growth in the province of North Sumatra is the total population.